Determination of Business Location by Using Analytical Hierarchy Process (AHP) and Weighted Product (WP) - Embun Fajar Wati; Elvi Sunita Perangin-Angin (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Information technology that is currently developing provides opportunities for business actors to develop their business. One of the factors that make a business grow is the location of the business. It is not easy to determine the appropriate business location, so various selections are needed so as to be able to measure the feasibility of the location. The existence of a decision support system can assist in making decisions about determining the location. The method chosen is the AHP method combined with the WP method. To get the value calculated by the AHP method, data collection by interview and observation was used. The literature study is used in the calculation stages with the AHP and WP methods. The use of a combination of AHP and WP methods in determining the location of the business gives a ranking result, with the highest score achieved by the Royal location of 0.617 and the lowest value achieved by the Poris location of 0.094. After observing the new location, Royal for 3 months, there was an increase in sales in the first month by 3 million/15%, in the 2nd month by 4 million/19% and in the 3rd month by 7 million/30%